Unrelated umbilical cord blood transplantation for children with hereditary leukodystrophy: A retrospective study - Wang, Ping; Du, Xiaonan; Shen, Quanli; Jiang, Wenjin; Shen, Chen; Wang, Hongsheng; Zhou, Shuizhen; Wang, Yi; Qian, Xiaowen; Zhai, Xiaowen (Frontiers in Neurology, 2022)
Objective: To analyze the efficiency of unrelated umbilical cord blood transplantation (UCBT) in the treatment of hereditary leukodystrophy following busulfan- and cyclophosphamide-based myeloablative chemotherapy. Methods: A retrospective study was performed in patients with hereditary leukodystrophy who underwent UCBT after myeloablative chemotherapy between April 2015 and March 2020. Results: The study cohort included 12 pediatric patients (ten males), nine with cerebral adrenoleukodystrophy (ALD) and three with juvenile globoid cell leukodystrophy (GLD). All received HLA-matched or partially mismatched unrelated UCBT. There were no cases of graft rejection. Median neutrophil engraftment time was 20 days [12–33 days] and median platelet engraftment time was 29 days [14–65 days]. Median follow-up was 36 months [1–86 months], and the overall survival rate for patients with cerebral ALD and juvenile GLD after UCBT was 77.8% (7/9) and 100% (3/3) respectively. In patients with ALD, although lipid profiles (serum very-long-chain fatty acid) were improved post-UCBT, six patients demonstrated worse neurologic function score and performance status post-UCBT, and six patients had higher Loes scores at last follow-up compared with baseline. In patients with juvenile GLD, all patients showed stable neurologic function score and performance status despite the Loes score of one patient increased slightly after transplantation. Conclusion: In patients with cerebral ALD, patients with no or mild neurological symptoms can benefit from UCBT, while UCBT cannot reverse advanced disease. In patients with juvenile GLD, UCBT is safe and contributes to stabilize neurological function.